Potencial de propagación por estacas de Elaeagia uxpanapensis (Rubiaceae) - Brenes, Liz; Di Stéfano G., José F. (Revista de Biología Tropical, 1995)
Cuuings (n=5, 30 cm long and 2-6 cm in diameter) from low branches of nn Elaeagia uxpanapensis tree (15 m tall and 24 cm DBH), were planted in a greenhouse aﬂer bEing treated with fungicides but no growth regulators. After 23 weeks, more than 60% developed buds, and 40%, leaves. SeveraJ produced rols (less Than 5 mm long) or calluses. Those with greater biomass and cul from the basal portion of (the branch, tended to perform better.